2022
DOI: 10.1111/joa.13712
|View full text |Cite
|
Sign up to set email alerts
|

Ovary structure and symbiotic associates of a ground mealybug, Rhizoecus albidus (Hemiptera, Coccomorpha: Rhizoecidae) and their phylogenetic implications

Abstract: The ovary structure and the organization of its symbiotic system of the ground mealybug, Rhizoecus albidus (Rhizoecidae), were examined by means of microscopic and molecular methods. Each of the paired elongated ovaries of R. albidus is composed of circa one hundred short telotrophic-meroistic ovarioles, which are radially arranged along the distal part of the lateral oviduct. Analysis of serial sections revealed that each ovariole contains four germ cells: three trophocytes (nurse cells) occupying the trophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In contrast to infection at the posterior pole of the oocyte, infection at the anterior pole of the oocyte is somewhat unique among insects. For example, in the ground mealybug Rhizoecus albidus, after leaving the bacteriocytes, Brownia rhizoecola migrates toward the ovaries and infects the anterior pole of the oocyte (109). This transmission strategy also occurs in the mealybugs Phenacoccinae and Pseudococcidae (64,121); the eriococcids Greenisca brachypodii, Acanthococcus aceris, and Gossyparia spuria (65,67); and Puto superbus (Putoidae) (110).…”
Section: Bacteriocyte Adaptation For Symbiont Transmissionmentioning
confidence: 99%
“…In contrast to infection at the posterior pole of the oocyte, infection at the anterior pole of the oocyte is somewhat unique among insects. For example, in the ground mealybug Rhizoecus albidus, after leaving the bacteriocytes, Brownia rhizoecola migrates toward the ovaries and infects the anterior pole of the oocyte (109). This transmission strategy also occurs in the mealybugs Phenacoccinae and Pseudococcidae (64,121); the eriococcids Greenisca brachypodii, Acanthococcus aceris, and Gossyparia spuria (65,67); and Puto superbus (Putoidae) (110).…”
Section: Bacteriocyte Adaptation For Symbiont Transmissionmentioning
confidence: 99%
“…Its phylogeny and classification are still under discussion; however, the 18S rRNA-based phylogeny of scale insects suggests a paraphyletic origin of eriococcids [11,12]. Previous studies showed that analyses of scale insect symbiotic microorganisms might help resolve relationships within and among Coccoidea families [13,14]. Results of studies on symbionts of Eriococcidae, although few, also indicate their diversity [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%